Zachování architektonické kvality a dlouhodobé životnosti železobetonových konstrukcí použitím galvanického povlakování výztuže na bázi Zn a Ni - Steinerová, Veronika (České vysoké učení technické v Praze, 2025)
Disertační práce se zabývá zvyšováním udržitelnosti železobetonových konstrukcí prostřednictvím ochrany ocelové výztuže proti korozi a možností snížení betonového krytí. Experimentálně byly testovány čtyři typy povlaků (galvanický zinkový, zinkoniklový, niklový a žárově zinkovaný) z hlediska korozní odolnosti a soudržnosti s betonem. Následné environmentální hodnocení tří typů deskových konstrukcí pomocí LCA ukázalo, že žárově zinkovaná výztuž výrazně prodlužuje životnost konstrukce s minimálním navýšením ekologické zátěže. Výsledky potvrzují, že optimalizace návrhu a vhodná volba povrchové úpravy výztuže mohou významně přispět ke zvýšení životnosti a udržitelnosti železobetonových konstrukcí.

The dissertation deals with increasing the sustainability of reinforced concrete structures by protecting steel reinforcement against corrosion and the possibility of reducing the concrete cover. Four types of coatings (galvanic zinc, zinc-nickel, nickel and hot-dip galvanized) were experimentally tested in terms of corrosion resistance and cohesion with concrete. The subsequent environmental assessment of three types of plate structures using LCA showed that hot-dip galvanized reinforcement significantly extends the service life of the structure with a minimal increase in the environmental burden. The results confirm that design optimization and appropriate choice of reinforcement surface treatment can significantly contribute to increasing the service life and sustainability of reinforced concrete structures.
Preservation of architectural quality and long-term durability of reinforced concrete structures by using galvanic coating of reinforcement based on Zn and Ni
Keywords: železobetonová konstrukce; protikorozní ochrana; galvanické povlaky; žárové zinkování; LCA; environmentální dopad; udržitelnost; reinforced concrete structure; corrosion protection; galvanic coatings; hot-dip galvanizing; LCA; environmental impact; sustainability